COMPREHENSIVE GUIDANCE AND COUNSELING FOR GIFTED CHILDREN THROUGH THE APPLICATION OF MILGRAM’S MODEL IN ACCELERATION-INCLUSION SETTING - Suherman, Yuyus; Kartadinata, Sunaryo; Yusuf, Syamsu; Alimin, Zaenal (UPI Press, 2015)
Acceleration program is claimed to be designated for gifted children. However, the implementation of the program is still considered sporadic and exclusive. This study aims at developping a comprehensive guidance and councelling for gifted child using Molgram’s model in acceleration inclusion setting. The research question is “ how is the development of comprehensive guidance and counseling for gifted children through Milgram’s model in acceleration-inclusion setting applicable and affective?